Digital makeup - Chua, Zi Jian (Nanyang Technological University, 2024)
In today’s progressively digitized world, social media has become the most common platform for people to share their lives and foster connections with others. It is not difficult to find people on social media posting their portrait and self-portrait photographs, and this leads to the increasing demand for photo-editing apps which help them to beautify their photos. However, the majority of the tools are designed for only editing raster images and it is well known that vector graphics provide several practical benefits over raster graphics, including sparse representation, compact storage, geometric editability, information reuse and resolution-independence.